Presence of Cotylophoron sp in bovine of the province of Moyobamba, Peru - Rojas H., Kelwin (2015)
The aim of this study was to determine the presence of Cotylophorum sp in cattle in six districts of the province of Moyobamba, Peru. A total of 411 faecal samples of cattle aged 1.5 to 8 years between October and November 2011 were collected. The samples were processed by the method of feacal sedimentation. The results showed the presence of eggs of Cotylophoron sp, with a prevalence of 55%. No statistically difference was found between the variables age, sex and place of origin and the presence of Cotylophoron sp.